Upaya Pencegahan Kejahatan White Collar Crime - Cindy Tifani; Dina Indriani (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2024)
The purpose of this research is to describe the efforts to prevent White Collar Crime. The method of writing this article is done by library research. Library research is a series of activities related to library data collection, reading and recording, and research data management methods. The results of this study are efforts to prevent white collar crime can be done by cooperation between the community, government and law enforcement officials.